Hyperpathia in the central cervical cord syndrome. Issue 4 (August 1973) - Hopkins, Anthony; Rudge, Peter
Abstract : Seven patients are described with hyperextension or flexion injury to the cervical cord. They illustrate the symptoms and signs previously associated with damage to the centre of the cord, in that weakness is greater in the upper limbs than the lower. We do not believe that the relative sparing of the legs can be accounted for on the basis that corticospinal fibres passing to the lumbar anterior horn cells lie laterally in the pyramidal tract, as has previously been suggested by Schneider, Cherry, and Pantek (1954) as there is no evidence that there is such lamination in man. Severe pain in the shoulders and arms was a major symptom in six of the patients, even in those with relatively minor injuries. The nature of this pain was initially often not recognized.